2008
DOI: 10.1111/j.1365-2966.2007.12696.x
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray emissions of highly charged Si vii-Si xii in cool star - Procyon

Abstract: Different observation data for cool star – Procyon (Obs_IDs of 63, 1461 and 1224) available from Chandra Public Data Archive were co‐added and analysed. Emissivities of emission lines of highly charged silicon ions (Si vii–Si xii) were calculated over temperatures by adopting the published data of Liang et al.. Using the emission measure derived by Raassen et al., the theoretical line fluxes are predicted, and the theoretical spectra are constructed by assuming the Gaussian profile with instrumental broadening… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…In the present work, we extract the line flux as done in the work of Liang & Zhao (2008) at the wavelengths as listed in Table 4. Table 4 Prominent Soft X-ray Lines and their Intensity Ratios (Relative to that of the Line at 58.963 Å) Recorded in Solar (Acton et al 1985) and Procyon (Raassen et al 2002) Because of low count rates in the Procyon observations, errors are found to be relatively large.…”
Section: Procyonmentioning
confidence: 99%
“…In the present work, we extract the line flux as done in the work of Liang & Zhao (2008) at the wavelengths as listed in Table 4. Table 4 Prominent Soft X-ray Lines and their Intensity Ratios (Relative to that of the Line at 58.963 Å) Recorded in Solar (Acton et al 1985) and Procyon (Raassen et al 2002) Because of low count rates in the Procyon observations, errors are found to be relatively large.…”
Section: Procyonmentioning
confidence: 99%
“…Although FAC was developed only rather recently, it has already been used extensively for the calculation of atomic data [34][35][36]. The recent measurement of the radiative decay rate of the (2s 2 2p 5 3/2 3s 1/2 ) J =2 level [24] provided a first test of FAC calculations of radiative rates, and excellent agreement between the calculated value of 2.06 × 10 5 s −1 and the measured value of (2.04 +0.03 −0.09 ) × 10 5 s −1 was found.…”
Section: Theoretical Techniquesmentioning
confidence: 99%